THE CULT OF THE QUEEN OF EARTH IN THE ANCIENT SLAVIC MYTHOLOGY - Матюхіна, О. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article aims at the philosophical analysis of the modern Ukrainian Education Reformation experience for the last decade.